Les structures évolutionnaires de la résilience - Philippe Woloszyn (VertigO)
The development of resilience systemic approaches centered on complex socio-ecological systems attempts to reconcile physical and social dimensions of this concept. Indeed, sustainable development calls for the coexistence not only of economic and social objectives, but also of ecological constraints, involving specific action and inertia scales. The analysis of the temporal scales of the manifestations of these constraints and objectives reveals that action policies that satisfy all the properties of sustainability are therefore shared between several evolution scales of each of the economic, social or ecological subsystems of sustainable development. This raises number of questions : How to develop an integrated analysis of the resilience of territories while respecting the temporality of sustainable development standards ? What are the temporal dimensions of resilience indicators ? How do they relate to governance and decision-making ? To answer these questions, which are central to resilience problematic, we deal with the question of the differential temporality between economic, social and ecological systems, by developing an inductive model in the three dimensions of sustainable development, with applying it to a specific case study, the drought in the United States which occurred in 2012. We will then examine the resilience process related to this event in the frame of evolutionary systems theory.